Hotel "Sand". St. Ann's, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
A photograph of Hotel Sand which was once located in St. Ann's, Trinidad.
Colour: Black and white; Style: Landscape; Other: Bordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--St. Ann's; Hotels--Trinidad and Tobago; Architecture--Trinidad and Tobago; Hospitality industry--Trinidad and Tobago